Accounting and Analytical Support for Cost Controlling in Livestock Production under ESG Constraints: Evidence from European Countries and Kazakhstan - Ayagoz, Orazbayeva; Aizhan, Ismailova; Aliya, Ismailova (Assets: Jurnal Akuntansi dan Pendidikan, 2026)
Livestock production plays a significant role in greenhouse gas emissions, creating increasing pressure to integrate environmental, social, and governance (ESG) considerations into cost-controlling and accounting systems. This study examines how governance effectiveness, production scale, and structural characteristics shape livestock emission intensity per head under ESG-related constraints, using a comparative framework covering European Union countries and Kazakhstan. The analysis combines descriptive statistics, three-dimensional visualization, panel regression modeling, and cluster analysis based on country-level panel data for 2000–2023. The results indicate substantial heterogeneity in emission intensity across EU member states and a persistent divergence between the EU median and Kazakhstan. Panel regression findings show that production scale variables dominate the determinants of emission intensity, while governance effectiveness plays a statistically significant but secondary role. Larger herd size is associated with lower emissions per head, suggesting scale-related efficiency gains. Cluster analysis further reveals distinct ESG–emissions groupings, with Kazakhstan positioned outside the main EU clusters. The findings demonstrate that effective ESG integration in livestock cost controlling requires accounting–analytical systems that jointly consider governance conditions, production scale, and structural differences rather than relying on uniform benchmarks or institutional indicators alone.